Mathematical Critical Thinking Ability in Solving Open-Ended Questions Viewed from Students’ Curiosity - Afifah, Siti Atiatul; Agoestanto, Arief (Department of Mathematics, Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the effect of the level of curiosity on students' mathematical critical thinking abilities in solving open-ended problems and describe the students' mathematical critical thinking skills in solving open-ended problems in terms of students' level of curiosity. This study was a mixed-methods study with sequential explanatory design. The results showed that (1) there was a significant influence between students 'curiosity on students' mathematical critical thinking abilities in solving open-ended problems, and (2) subjects at high levels of curiosity tended to be able to all the sub-indicators of critical thinking skills. Subjects at a moderate level of curiosity tend to be less able to sub-indicators to use facts to be applied in concepts/formulas appropriately, draw initial conclusions in each step of completion, and work on problems with coherent steps. Subjects at a low level of curiosity tend to be unable to sub-indicators to use facts to be applied in concepts or formulas appropriately and tend to be less able to sub-indicators formulate problem questions, draw initial conclusions in each step of the solution, work on problems with coherent steps, and write down the steps to solve the problems that have been found.